Effects of turbidity on the reactive distance, search time, and foraging success of juvenile Atlantic cod (Gadus morhua) - Meager, J J; Solbakken, T; Utne-Palm, A C; Oen, T (Canadian Journal of Fisheries and Aquatic Sciences, 2005)
We investigated the effects of turbidity on the foraging behaviour of juvenile Atlantic cod (Gadus morhua) on mysid prey (Praunus neglectus) in the laboratory. The influence of turbidity on vision and chemoreception was examined by measuring reactive distances and search times to visual, chemical, and visual–chemical prey cues over turbidity levels ranging from 0.4 to 17·m–1 (beam attenuation·m–1). We also compared foraging rates of juvenile cod on mysids in highly turbid water and clear water under well lit and totally dark conditions. Juvenile cod using chemical cues were able to locate mysids from significantly longer distances than when only visual cues were available. Turbidity did not affect reactive distance to chemical cues, and had only a weak negative effect on reactive distance to visual and visual–chemical cues. Search time was variable, but tended to increase with turbidity. Turbidity did not affect predation rates on free-ranging mysids, but predation rates were significantly lower in dark conditions than in well lit conditions. We suggest that juvenile cod use chemoreception in conjunction with vision (at close ranges) to locate prey in highly turbid water.